The Effect Of Digital Storybook Media In Anticipating Bullying In Children Aged 5-6 Years Old - Muthmainnah, Azizah; Telaumbanua, Putri; Shaleha, Kharida; Lase, Aritina; Tafonao, Tira (Outline Publisher, 2026)
Bullying behaviors have emerged as an early social problem among children aged five to six years, making preventive interventions in early childhood education essential. This study examined the effect of digital storybook media on children’s knowledge, attitudes, and ability to anticipate bullying situations. A quantitative approach was employed using a quasi-experimental pretest–posttest control group design. Sixty kindergarten children aged five to six years were selected and divided into an experimental group and a control group. The experimental group received an intervention using interactive digital storybooks with anti-bullying themes over twelve sessions, while the control group participated in conventional learning activities. Data were collected through a bullying knowledge test, an anti-bullying attitude scale, and behavioral observation of bullying anticipation skills. Statistical analyses included descriptive statistics, paired sample tests, independent sample tests, and analysis of covariance. The results showed that children who used digital storybooks demonstrated significantly higher improvements in bullying knowledge, anti-bullying attitudes, and anticipation skills compared to children in the control group. The magnitude of the effect was substantial across all measured variables, indicating strong practical significance. The findings suggested that digital storybooks effectively supported cognitive, affective, and behavioral learning processes related to bullying prevention. In conclusion, digital storybook media constituted an effective and engaging educational tool for strengthening early childhood anti-bullying education and could be integrated into early childhood learning programs to promote positive social behavior.